2020
DOI: 10.1111/jog.14200
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the associations of Reid Colposcopic Index and Swede Score with cervical histology

Abstract: Aim Cervical cancer, the fourth most common cancer in women, is preventable. Colposcopy and colposcopic scoring systems are helpful tools to guide the treatment of precancerous lesions. This study was done to compare the association between Reid colposcopic index (RCI) and Swede score. Methods This prospective study enrolled 159 subjects aged 18 years or over with abnormal pap smears or high‐risk HPV (types 16 and/or 18). All women underwent colposcopies, and the findings were classified by RCI and Swede score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…The colposcopic impression diagnosis made on the basis of subjective judgement is re ective of cervical appearance. However, few publications have reported discrepancies between different HPV genotypes, and the correlation between colposcopic ndings and HPV genotypes is controversial (13,14). In this study, we found that the sensitivity of colposcopic impression in the detection of cervical HSILs was signi cantly different among different HPV type groups; it was the highest in HPV16-positive patients, followed by HPV18-positive patients, and was the lowest in HPV52-positive patients.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The colposcopic impression diagnosis made on the basis of subjective judgement is re ective of cervical appearance. However, few publications have reported discrepancies between different HPV genotypes, and the correlation between colposcopic ndings and HPV genotypes is controversial (13,14). In this study, we found that the sensitivity of colposcopic impression in the detection of cervical HSILs was signi cantly different among different HPV type groups; it was the highest in HPV16-positive patients, followed by HPV18-positive patients, and was the lowest in HPV52-positive patients.…”
Section: Discussionmentioning
confidence: 58%
“…For all the systems, colposcopic ndings are classi ed according to the severity of cervical lesions, such as normal/benign lesions, low-grade squamous intraepithelial lesions (LSILs), high-grade squamous intraepithelial lesions (HSILs), and invasive lesions. However, the correlation between colposcopic ndings and HPV types has never been examined (13,14). Some research studies have evaluated the different appearances of the cervix caused by different HPV genotypes, but the results were inconsistent (17).…”
Section: Introductionmentioning
confidence: 99%
“…The colposcopic impression diagnosis made on the basis of subjective judgement is reflective of cervical appearance. However, few publications have reported discrepancies between different HPV genotypes, and the correlation between colposcopic findings and HPV genotypes is controversial [ 13 , 14 ]. In this study, we found that the sensitivity of colposcopic impression in the detection of cervical HSILs was significantly different among different HPV type groups; it was the highest in HPV16-positive patients, followed by HPV18-positive patients, and was the lowest in HPV52-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…By applying acetic acid (3–5%) and Lugol’s iodine, a colposcopist can detect abnormalities in cervical visual appearance based on changes in the epithelium and blood vessels [ 10 ]. As colposcopy is a subjective procedure, some colposcopic scoring and nomenclature systems have been introduced worldwide [ 11 13 ]. Among them, the latest and most popular is the International Federation of Cervical Pathology and Colposcopy (IFCPC) nomenclature published in 2011, which was also the important basis for the 2018 American Society for Colposcopy and Cervical Pathology (ASCCP) Colposcopy Standards recommendations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation